Identification of 2127 new HLA class I alleles in potential stem cell donors from Germany, the United States and Poland. Issue 3 (March 2014) - Hernández‐Frederick, C. J.; Giani, A. S.; Cereb, N.; Sauter, J.; Silva‐González, R.; Pingel, J.; Schmidt, A. H.; Ehninger, G.; Yang, S. Y.
Abstract We describe 2127 new human leukocyte antigen (HLA) class I alleles found in registered stem cell donors. These alleles represent 28.9% of the currently known class I alleles. Comparing new allele sequences to homologous sequences, we found 68.1% nonsynonymous nucleotide substitutions, 28.9% silent mutations and 3.0% nonsense mutations. Many substitutions occurred at positions that have not been known to be polymorphic before. A large number of HLA alleles and nucleotide variations underline the extreme diversity of the HLA system. Strikingly, 156 new alleles were found not only multiple times, but also in carriers of various parentage, suggesting that some new alleles are not necessarily rare. Moreover, new alleles were found especially often in minority donors. This emphasizes the benefits of specifically recruiting such groups of individuals.